An examination of the relationship between burnout and grit in college athletes - Barcza-Renner, K.; Shipherd, A. M.; Basevitch, I. (Asian Journal of Sport and Exercise Psychology, 2024)
Burnout symptoms are a detrimental concern many athletes have at some point throughout their athletic careers. In order to assist athletes with performing at their optimal level, there is a need to better understand the burnout phenomena and the ways it can interact with other performance variables, such as grit. Given that grit is a predictor of success in a variety of domains (e.g., Duckworth & Yeager, 2015; Eskreis-Winkler et al., 2014; Fernández-Martin et al., 2020), the purpose of the study was to examine the relationship between grit and burnout. It was hypothesized that there would be an inverse correlation between grit and burnout. Grit and burnout data was collected from Division I student-athletes (n = 241) towards the end of their competitive seasons. Further, the student-athletes year in college was considered as a potential moderator between grit and burnout. The results indicated that student-athletes who scored higher in grit, also scored higher in burnout, hence the hypothesis was not supported. Additionally, there was a stronger positive relationship between grit and burnout for first-year students and sophomores, when compared with juniors and seniors. It is plausible athletes who are grittier are more likely to persevere through stress and challenges, including burnout symptoms, especially during their first two years of college. Athletes higher in grit may also be investing more effort into their sport, which could be increasing symptoms of burnout, as well. The results of this study warrant further investigation to clarify the interaction between grit and athlete burnout.